Seroepidemiological study of Herpes simplex virus 2 in human immuno deficiency virus-positive individuals attending a tertiary care hospital of South India - Singh, Manoj Kumar; Halthur, Krishna Santosh; Kandati, Jithendra; Narukuru, Premanadam; Basava, Siva Prasad Reddy (International Journal Of Community Medicine And Public Health, 2016)
Background: Herpes Simplex Virus-2 (HSV-2) infection is widely studied and associated disease in human immuno deficiency virus-positive (HIV-positive) individuals. The diagnosis of HSV is difficult as the presentations are atypical. Studies have confirmed that HSV-2 infection increases the risk of HIV acquisition by 2-3 folds. The aim of the study was to estimate the seroprevalence of HSV-2 and its association with age, sex and behavioral characters among HIV-infected individuals attending a tertiary care hospital. Methods: Serum samples from 150 HIV positive patients were collected and screened for HSV-2 Ig G antibodies by indirect ELISA. The cut off index (COI) of each serum sample was determined by dividing the OD which was obtained for that serum sample, by the average OD of the cutoff serum. A COI below or equal to 1 was considered as negative and that above 1.1 was considered as positive. Results: The overall seroprevalence of HSV-2 in the study was 44% (95% CI: 36-52%) with more in men than women. Out of 92 men, 42 (45.65%) were HSV positive and 24 (41.38%) of 58 female were positive. Statistical significance was observed in participants who had past history of sexually transmitted disease and who had multiple sexual partners (≥11) making as risk factors for HSV-2 seropositivity. Genital herpes was reported in 41 of 150 participants and seropositivity was 51.22% indicating the lack of awareness and most of the infections are asymptomatic. Conclusions: Our study demonstrated a clear increase in seroprevalence of HSV-2 in HIV-infected individuals. Findings of our study have relevant public implications and strongly suggest the implementation of interventions in sexually transmitted infections to reduce the prevalence of HSV-2 and associated HIV transmission. As most of the infections of HSV are asymptomatic a continuous program for the screening of HSV in all cases of STD’s must be made to reduce the chances of acquisition of HIV and others.